Взаємодія НДІ з промисловими підприємствами як засіб підвищення ефективності виробництва - Кучинський, Володимир Анатолійович; Подрез, Ольга Іванівна (НТУ "ХПІ", 2015)
На базі аналізу діяльності галузевих НДІ та промислових підприємств, запропоновано механізм взаємодії органів державного управління, науково-дослідних інститутів та промислових підприємств, сутність якого полягає в розробці стратегічних планів діяльності галузевих інститутів, узгодженості їх з органами влади та промисловими підприємствами (бізнес-структурами), обґрунтуванні джерел фінансування НДІ та оцінювання ефективності результатів впровадження наукових розробок у діяльність бізнес-структур.

On the basis of analysis of Sciences of Ukraine, industrial research institutes and industry identified problems of innovative development of industry. They are the lack of a clear system of planning of scientific and technological development of certain sectors of t he economy, uncertainty priority areas of scientific and technological activities, lack of sufficient funding as NAS of Ukraine and industrial research institutes, lack of a strategic plan for orders from the government and businesses to conduct industry SRI fundamental and applied research, lack of sufficient encouragement and stimulation of researchers, and so on. To form the medium- and long-term forecasts of priority research areas proposed in the article to create a national research university with regional forecasting centers of scientific and technological development. In addition, the article the mechanism of interaction between government, research institutes and industrial enterprises, the essence of which is to develop strategic plans of branch institutes, coordination them with the authorities and industrial enterprises (businesses), justification funding sources NDI and evaluating the effectiveness of the implementation of the results of scientific research activities in businesses.
NGO interaction with industry as a means of improving the efficiency of production
Keywords: науково-дослідний інститут; джерела фінансування; податкові пільги; технологічна відсталість; соціально-економічна ефективність; funding; tax incentives; technological backwardness